The tale of Mr. Tod - Potter, Beatrix, 1866-1943. ((New York) : Warne, 1987)
Peter Rabbit and Benjamin Bunny try to save a family of baby rabbits being kept in the fox's house by a badger who wants them for dinner.
3.7
K-3
Keywords: Animals -- Fiction; Animals -- Fiction; Rabbits -- Fiction; Foxes -- Fiction; Animals -- Fiction